Finite element approach to analyze structural discontinuities associated with ship hull - Hoque, Kazi Naimul; Islam, Md Shahidul (Journal of Naval Architecture and Marine Engineering, 2023)
The finite element method (FEM) is widely recognized as a powerful numerical analysis technique for approximating solutions in structural mechanics. Addressing the configuration of plate-type structures, particularly those with discontinuities, is crucial not only in ship and aircraft construction but also in various other fields. Structural discontinuities occur when there are sudden changes in the cross-section of structural members due to material imperfections or high-stress areas. This paper focuses on the fundamental principles of FEM for solving two-dimensional plane stress problems and analyzing stresses such as normal stress, shear stress, and von-mises stress at the four integration points (gauss points) in different sections of ship structures, particularly in vulnerable regions. To address structural discontinuity problems in various ship structures, a finite element program utilizing object-oriented techniques was developed, employing four-node quadrilateral elements. The analysis results of gauss point stresses obtained from the developed program were validated against a commercial finite element analysis software to ensure accuracy and reliability. Additionally, a mesh viewing program has been developed in the Python programming language to enable the visualization and analysis of the generated mesh using the developed object-oriented finite element program. J. Nav. Arch. Mar. Engg., Vol 20(2), December, 2023; p 1-14